Classic World War II Aircraft Cutaways - Gunston, Bill (London Osprey, 1995)
This work features the major cutaway types, republished after years in the archives. The cutaways are accompanied by photographs, individual specifications, and a history of each type. The book also contains information on the cutaway artists themselves.
Include Index, Appendix and Illustration
Keywords: Airplanes--Design and construction -- Airplanes, Military -- World War (1939-1945)